SPORTSKO-REKREATIVNI PROGRAMI KAO FAKTOR VALORIZACIJE TURISTIČKE PONUDE - Ivica Nikolić (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2005)
This survey is the result of a doctor's thesis at interdiscipline department for "Management in sport" at the University of Novi Sad in 2004 by mr Ivica Nikolić. The research has been done on the scientific understanding of sport and the world around us, known as a postpositive paradigm being characterised by multidimension, interdiscipline and as the triangulation aproach as well. Tourism represents significant and complex economic and social phenomena reflecting the level of socio-economic development of a country. Modern tourist offer necessarilly has to be of a certain quality to obtain better economic effects. High quality offer must provide a guest with cultural and profilactic way of resting (sports and recreation activities). It also contributes to a better mental and physical aspects of a personality. These offers are becoming more requested for which is in keeping with contemporary tourist motives. The main issue here explains how to increase the validity level of the offer through sports and recreation activities. The research subject is directed to various models of sports and recreation programs, sports facilities, means, beneficiairies, motives, attitudes, tourism and its offer and physical recreation activity. The objective was to determine, obtain and increase the offer such as physical activities and at the same time to apply effective methods by using sport and recreation. The basic hypothesis, defined as "zero" (Ho) says: "There is no significant statistic interaction between offer and sports activity." The ground methodology in data processing was based on a questionnaire having being related to potential and direct beneficiaries in tourist offer in Vojvodina. The conducted poll was presented through 64 variables based upon triangulation principals. Useful results confirmed the objective hypotesis and rejected "zero" one. On the ground of gained research results, we came to conclusion that sports and physical activities directly affects the quality of toursis offer measured by dependent variable.